Clozapine in drug induced psychosis in Parkinson's disease: a randomised, placebo controlled study with open follow up. Issue 5 (16th April 2004) - Pollak, P; Tison, F; Rascol, O; Destée, A; Péré, J J; Senard, J M; Durif, F; Bourdeix, I
Abstract : Objective: To compare the efficacy and safety of clozapine in drug induced psychosis in Parkinson's disease (PD). Methods: A four week, randomised, double blind, parallel comparison of clozapine and placebo, followed by a 12 week clozapine open period, plus a one month period after drug discontinuation, in 60 patients with PD. The primary efficacy outcome was the "clinical global impression scale" (CGI); the positive subscore of the "positive and negative syndrome scale" (PANSS) was used as the secondary efficacy parameter and the "unified Parkinson's disease rating scale" (UPDRS) and the "mini mental test examination" (MMSE) as safety outcomes. Results: The mean (SD) dosage of clozapine was 35.8 (12.5–50) mg at the end of the double blind period. The mean (SD) scores on the CGI improved by 1.8 (1.5) for the clozapine group compared with 0.6 (1.1) for the placebo group (p = 0.001). The mean (SD) positive subscore of PANSS improved by 5.6 (3.9) for the clozapine group (0.8 (2.8) for the placebo group; p < 0.0001). At the end of the open period, 25 patients had completely recovered from delusions and hallucinations, and 19 experienced a relapse within one month after the clozapine washout period. The UPDRS motor and MMSE mean scores did not change significantly in either group. Somnolence was more frequent with clozapine than with placebo. Conclusions: Clozapine at a mean dose lower than 50 mg/day improves drug induced psychosis in PD without significant worsening of motor function, and the effect wears off once the treatment stops.